AB0-Locus influences the Clot Structure Comment - Hackstein, Holger (Transfusionsmedizin, 2021)
CRIS-Team WoS Importer:2021-03-26

Acute Hemolytic Transfusion Reaction by an Anti-s Due to Delayed Type and Screen Procedures Until Occurrence of a Hemorrhagic Shock - Zimmermann, Robert; Strasser, Erwin; Hackstein, Holger (Transfusionsmedizin, 2019)
In the past decade, profound changes in the clinical practice of haemotherapy have occurred in most industrial countries, including Germany. Red blood cell (RBC) order procedures are performed more and more cautious. The utilization of RBC concentrates is strongly declining. At the same time, the number of patients for whom the preoperative or pre-interventional provision of cross-matched blood is not carried out despite planned surgery or intervention is also increasing. We report on a 71-year-old multimorbid patient with dilated cardiomyopathy, severely reduced cardiac reserve, a few weeks after valve replacement surgery, ongoing anticoagulation with heparin and diagnosed anemia with hemoglobin values between 7 and 8 g/dl. In this patient, a haemorrhagic shock was induced by a Forrest-II b haemorrhage from a duodenal ulcer after several days of in-patient treatment. In the context of emergency care, it turned out that all pre-transfusion diagnostics had been missed. The patient received uncross-matched red blood cell concentrates of blood group 0 Rh negative which unexpectedly triggered an acute haemolytic transfusion reaction. The reason was an irregular antibody against the antigen s from the MNSs blood group system that had not been identified before the transfusion. Acute hemolytic transfusion reactions outside the AB0 system are a rare, but nevertheless always threatening complication of the transfusion of uncrossmatched erythrocyte concentrates in life- threatening bleeding emergencies. The case shows that the desire to follow a restrictive transfusion practice must not lead to overlooking constellations in individual cases which, of course, require the timely performance of a pre-transfusional diagnostic procedure with blood group typing, antibody screening and antibody identification. In our opinion, the frequency of comparable events is increasing to an extent that suggests that such errors in the clinical treatment process should not only be dealt within CIRS systems but also recorded in haemovigilance systems.
CRIS-Team WoS Importer:2019-09-20

ADAR1 Is Required for Dendritic Cell Subset Homeostasis and Alveolar Macrophage Function - Baal, Nelli; Cunningham, Sarah; Obermann, Hannah-Lena; Thomas, Jenny; Lippitsch, Anne; Dietert, Kristina; Gruber, Achim D.; Kaufmann, Andreas; Michel, Gabriela; Nist, Andrea; Stiewe, Thorsten; Rupp, Oliver; et al. (Journal of Immunology, 2019)
RNA editing by adenosine deaminases acting on dsRNA (ADAR) has become of increasing medical relevance, particularly because aberrant ADAR1 activity has been associated with autoimmunity and malignancies. However, the role of ADAR1 in dendritic cells (DC), representing critical professional APCs, is unknown. We have established conditional murine CD11c Cre-mediated ADAR1 gene ablation, which did not induce general apoptosis in CD11c(+) cells but instead manifests in cell type-specific effects in DC subpopulations. Bone marrow-derived DC subset analysis revealed an incapacity to differentiate CD103 DC+ in both bulk bone marrow and purified pre-DC lineage progenitor assays. ADAR1 deficiency further resulted in a preferential systemic loss of CD8(+)/CD103(+) DCs, revealing critical dependency on ADAR1, whereas other DC subpopulations were moderately affected or unaffected. Additionally, alveolar macrophages were depleted and dysfunctional, resembling pulmonary alveolar proteinosis. These results reveal an unrecognized role of ADAR1 in DC subset homeostasis and unveils the cell type-specific effects of RNA editing.
CRIS-Team WoS Importer:2019-02-21

An Exploratory Study Using Next-Generation Sequencing to Identify Prothrombotic Variants in Patients with Cerebral Vein Thrombosis. - Kramer, Robert Anton; Zimmermann, Robert; Strobel, Julian; Achenbach, Susanne; Stroebel, Armin; Hackstein, Holger; Messerer, David Alexander Christian; Schneider, Sabine (International Journal of Molecular Sciences, 2023)
Prothrombotic hereditary risk factors for cerebral vein thrombosis (CVT) are of clinical interest to better understand the underlying pathophysiology and stratify patients for the risk of recurrence. This study explores prothrombotic risk factors in CVT patients. An initial screening in patients of the outpatient clinic of the Department of Transfusion Medicine and Hemostaseology of the University Hospital Erlangen, Germany, revealed 183 patients with a history of CVT. An initial screening identified a number of common prothrombic risk factors, including Factor V Leiden (rs6025) and Prothrombin G20210A (rs1799963). All patients without relevant findings (58 individuals) were invited to participate in a subsequent genetic analysis of 55 relevant genes using next-generation sequencing (NGS). Three intron variants (ADAMTS13: rs28446901, FN1: rs56380797, rs35343655) were identified to occur with a significantly higher frequency in the CVT patient cohort compared to the general European population. Furthermore, the combined prevalence of at least two of four potentially prothrombic variants (FGA (rs6050), F13A1 (rs5985), ITGB3 (rs5918), and PROCR (rs867186)) was significantly higher in the CVT subjects. The possible impact of the identified variants on CVT is discussed.
EVALuna2:535884

A simplified extracorporeal photopheresis procedure based on single high-dose ultraviolet A light irradiation shows similar in vitro efficacy - Buchele, Vera; Hackstein, Holger (Transfusion, 2020)
Background: Extracorporeal photopheresis (ECP) is one of the most widely used and effective cell-based therapies for the treatment of T-cell–mediated diseases. The patients' white blood cells (WBCs) are collected by apheresis and exposed to the photosensitizer 8-methoxypsoralen (8-MOP) and ultraviolet A (UVA) light before retransfusion. The UVA/8-MOP combination has been in use in ECP for more than 4 decades; however, whether ECP can be simplified by UVA light irradiation only has never been analyzed. Study Design and Methods: Peripheral blood mononuclear cells were treated with classical ECP or different UVA light doses only (UVAonly). Treatment efficacy was investigated by apoptosis induction in WBC subsets, inhibition of T-cell proliferation, and the ability of monocytes to induce allogeneic T-cell expansion and to respond to lipopolysaccharide and interferon-γ stimulation in vitro. Results: High-dose UVAonly treatment (5 J/cm2) was as efficient as ECP to induce apoptosis within 48 hours. UVAonly treatment modulated the composition of the surviving cells by improving monocyte survival and promoting CD8+ T-cell apoptosis. Both ECP and UVAonly treatment inhibited anti-CD3/anti-CD28 triggered T-cell proliferation. Interestingly, whereas ECP-treated monocytes exhibited a markedly reduced capacity to respond to stimulation and to induce allogeneic T-cell proliferation, UVAonly treatment preserved monocyte functionality to some degree. Conclusions: High-dose UVAonly and standard ECP showed comparable efficacy in inducing apoptosis and inhibiting direct T-cell proliferation. Hence, UVAonly treatment can be a simplified alternative to ECP therapy. Furthermore, increased monocyte survival with partially preserved functionality after UVAonly treatment may provide a novel method for immunoregulation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: apoptosis; extracorporeal photopheresis; UVA light

Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis - Voskens, Caroline; Stoica, Diane; Rosenberg, Marita; Vitali, Francesco; Zundler, Sebastian; Ganslmayer, Marion; Knott, Heike; Wiesinger, Manuel; Wunder, Jutta; Kummer, Mirko; Siegmund, Britta; Schnoy, Elisabeth; et al. (Gut, 2022)
Objective Ulcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available.
CRIS-Team WoS Importer:2022-04-29

Biomimetic Magnetic Particles for the Removal of Gram-Positive Bacteria and Lipoteichoic Acid. - Friedrich, Bernhard; Eichermüller, Julia; Bogdan, Christian; Cunningham, Sarah; Hackstein, Holger; Strauss, Richard; Alexiou, Christoph; Lyer, Stefan; Tietze, Rainer (Pharmaceutics, 2022)
Gram+ bacteria are very common in clinical medicine and responsible for a large number of infectious diseases. For example, Gram+ bacteria play a major role in causing bloodstream infections and sepsis. Therefore, the detection of Gram+ bacteria is of great importance for the diagnosis and treatment of infectious diseases. Furthermore, these bacteria are often present in biofilms that cover implants. Recent research work has mainly focused on the biologic activity and removal of Gram-negative bacteria or bacterial components such as lipopolysaccharides (LPS). In contrast, the effects of lipoteichoic acid (LTA) have been less well studied so the relevance of their removal from body fluids is possibly underestimated. To address this topic, we evaluated superparamagnetic iron oxide particles (SPION) carrying different peptides derived from the innate immune receptor (GP-340) for their ability to bind and remove Gram+ bacteria and LTA from different media. Our results show that, beyond S. aureus, effective agglutinating and removing of S. pneumoniae was possible. Furthermore, we were able to show for the first time that this was possible with LTA alone and that the magnetic removal of bacteria was also efficient under flow conditions. We also found that this method was able to capture Stapyhylococcus aureus from platelet concentrates, which can help to enhance the sensitivity of microbiological diagnostics, quality control measures, and blood product safety.
EVALuna2:508460

CD11c(+) dendritic cells mediate antigen-specific suppression in extracorporeal photopheresis - Hackstein, Holger; Kalina, A.; Dorn, B.; Keil, I. S.; Baal, N.; Michel, G.; Brendel, C.; Neubauer, A.; Jakob, T.; Bein, Gregor (Clinical and Experimental Immunology, 2020)
Extracorporeal photopheresis (ECP) represents one of the most widespread and effective cell therapies for graft-versus-host disease and other T cell-mediated disorders. However, the key factors affecting the therapeutic efficacy of ECP remain unclear. We hypothesized that therapeutic effects are mediated by ECP-treated antigen-presenting dendritic cells (DC). To test this hypothesis, we used the experimental model of contact hypersensitivity (CHS). The ECP's therapeutic activity improved when the total cell dose of the ECP-treated cells was increased. We used different haptens during sensitization to demonstrate that the anti-inflammatory activity of ECP is antigen-specific. This confirmed the hypothesis that professional antigen-presenting cells are involved in the mode of action. Also, the ECP's therapeutic activity was abrogated by the depletion of CD11c(+) DC, which represents fewer than 1% of all the ECP-exposed cells. Finally, we confirm the critical importance of CD11c(+) DC for ECP activity by showing that only a few purified CD11c(+) DC are sufficient to mediate its therapeutic effect. The finding that ECP-treated, physiological antigen-presenting DC alone mediate antigen-specific modulation of a pathological immune response may result in better-targeted interventions when treating patients.
CRIS-Team WoS Importer:2020-11-27

CD71 surface analysis of T cells: a simple alternative for extracorporeal photopheresis quality control - Schwab, Laura; Michel, Gabriela; Bein, Gregor; Hackstein, Holger (Vox Sanguinis, 2019)
Background: Extracorporeal photopheresis (ECP) is a leukapheresis-based cellular therapy that is used with increasing frequency worldwide to treat various T-cell-mediated diseases. Currently, the inhibition of T-cell proliferation after photopheresis is analysed frequently using time-consuming assays including radioactive thymidine assays or carboxyfluorescein succinimidyl ester (CFSE) staining. We investigated whether simple surface T-cell staining using surrogate markers of T-cell proliferation can replace time-consuming measurement of T-cell proliferation in ECP quality control. Study design and methods: T-cell activation markers were investigated by flow cytometry after ECP. Candidates were validated by direct comparison with the classical CFSE T-cell proliferation inhibition test and apoptosis staining. Finally, surface T-cell staining was performed in patient samples in comparison with classical methods. Results: CD71 expression exhibited the fastest and most robust upregulation, which was detectable as early as 6–8 h after T-cell stimulation and almost completely abrogated by ECP. In a direct comparison with the CFSE T-cell proliferation assay, suppression of CD71 expression after ECP was almost identical and detectable as early as 16 h after stimulation in peripheral blood mononuclear cells of healthy donors. Furthermore, in direct comparison with classical apoptosis staining, the inhibition delta of CD71 after ECP was significantly higher. Moreover, in patients under T-cell suppressive therapy, T-cell-dependent CFSE and CD71 assays exhibited decreased sensitivity to detect ECP treatment and were inferior in comparison to apoptosis staining. Conclusion: Surface CD71 analysis represents a very simple quality control alternative to detect ECP-mediated T-cell proliferation inhibition in normal PBMC samples devoid of T-cell suppressive drugs.
CRIS-Team Scopus Importer:2019-11-19
Keywords: CD71; extracorporeal photopheresis; flow cytometry

CD71 surface analysis of T cells: a simple alternative for extracorporeal photopheresis quality control - Schwab, Laura; Michel, Gabriela; Bein, Gregor; Hackstein, Holger (Vox Sanguinis, 2020)
BACKGROUND: Extracorporeal photopheresis (ECP) is a leukapheresis-based cellular therapy that is used with increasing frequency worldwide to treat various T-cell-mediated diseases. Currently, the inhibition of T-cell proliferation after photopheresis is analysed frequently using time-consuming assays including radioactive thymidine assays or carboxyfluorescein succinimidyl ester (CFSE) staining. We investigated whether simple surface T-cell staining using surrogate markers of T-cell proliferation can replace time-consuming measurement of T-cell proliferation in ECP quality control. STUDY DESIGN AND METHODS: T-cell activation markers were investigated by flow cytometry after ECP. Candidates were validated by direct comparison with the classical CFSE T-cell proliferation inhibition test and apoptosis staining. Finally, surface T-cell staining was performed in patient samples in comparison with classical methods. RESULTS: CD71 expression exhibited the fastest and most robust upregulation, which was detectable as early as 6-8 h after T-cell stimulation and almost completely abrogated by ECP. In a direct comparison with the CFSE T-cell proliferation assay, suppression of CD71 expression after ECP was almost identical and detectable as early as 16 h after stimulation in peripheral blood mononuclear cells of healthy donors. Furthermore, in direct comparison with classical apoptosis staining, the inhibition delta of CD71 after ECP was significantly higher. Moreover, in patients under T-cell suppressive therapy, T-cell-dependent CFSE and CD71 assays exhibited decreased sensitivity to detect ECP treatment and were inferior in comparison to apoptosis staining. CONCLUSION: Surface CD71 analysis represents a very simple quality control alternative to detect ECP-mediated T-cell proliferation inhibition in normal PBMC samples devoid of T-cell suppressive drugs.
EVALuna2:213423

Characterization of mast cell-derived rRNA-containing microvesicles and their inflammatory impact on endothelial cells - Elsemueller, Ann-Kathrin; Tomalla, Vanessa; Gaertner, Ulrich; Troidl, Kerstin; Jeratsch, Sylvia; Graumann, Johannes; Baal, Nelli; Hackstein, Holger; Lasch, Manuel; Deindl, Elisabeth; Preissner, Klaus T.; Fischer, Silvia (The FASEB Journal, 2019)
Tissue-resident mast cells (MCs) are well known for their role in inflammatory responses and allergic and anaphylactic reactions, but they also contribute to processes of arterial remodeling. Although ribosomes and cytosolic RNAs are located around secretory granules in mature MCs, their functional role in MC responses remains unexplored. Previous studies by our group characterized extracellular RNA (eRNA) as an inflammatory and pathogenetic factor in vitro and in vivo. In the present study, RNA-containing MCs and eRNA were located in close proximity to growing collateral arteries in vivo. In vitro, various agonists were found to induce the degranulation of MCs and the concomitant release of eRNA in association with microvesicles (MVs). The liberation of eRNA from MCs was abolished by MC stabilizers or by preventing the increase of intracellular Ca2+ in MCs. eRNA was found to be mainly contained inside MVs, as demonstrated by electron microscopy and immunocytochemistry. The exposure to and the uptake of MC-released MVs by cultured endothelial cells increased their expression of cytokines, such as monocyte chemoattractant protein or IL-6, in a dose- and time-dependent manner. These results indicate that RNA-containing MC-derived MVs are likely to be involved in inflammatory responses, relevant, for example, to processes of vascular remodeling.
CRIS-Team WoS Importer:2019-04-12

Characterization of the impact of immune checkpoint inhibitors on platelet activation and aggregation - Schlüter, Julian; Cunningham, Sarah; Zimmermann, Robert; Achenbach, Susanne; Kramer, Rafaela; Erdmann, Michael; Beckmann, Matthias; Heinzerling, Lucie; Hackstein, Holger (Immunobiology, 2023)
Immune checkpoint inhibitors (ICIs) are effective oncological drugs which block cellular check-point receptors typically targeted by tumor immune evasion strategies. Despite their benefits, clinicians have reported treatment-associated thromboembolism during ICI therapy in recent years. Though several theories on this ICI-associated pathogenesis exist, the direct effects of ICIs on platelets remains unknown. We therefore investigated the potential direct and indirect effect of PD-1, PD-L1 and CTLA-4-targeting ICIs on platelet functionality in multifaceted in vitro experiments. Interestingly, we could not observe a clear effect of ICI on platelet aggregation and primary hemostasis in whole blood and platelet concentrate-based assays. Furthermore, the presence of ICIs in toll-like receptor stimulation had no significant impact on platelet surface marker expression. In a second approach, we investigated the indirect immunological impact of ICIs on platelet activation by exposing platelets to supernatants from ICI- and Staphylococcal enterotoxin B-exposed PBMCs. Whereas ICIs affected IL-2 levels in supernatants, we could not detect clear differences in the secretion of pro-thrombogenic factors and platelet responses. The obtained data suggest that the direct influence of ICIs on platelet activation or the influence of altered T cell function on platelet activation cannot be considered a major factor in the development of thrombotic events.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Immune checkpoint inhibitors; Platelet activation; Platelet function tests; Platelets; Thrombosis

Cord-blood-derived professional antigen-presenting cells: Functions and applications in current and prospective cell therapies - Cunningham, Sarah; Hackstein, Holger (International Journal of Molecular Sciences, 2021)
Human umbilical cord blood (UCB) represents a valuable source of hematopoietic stem cells, particularly for patients lacking a matching donor. UCB provides practical advantages, including a lower risk of graft-versus-host-disease and permissive human leukocyte antigen mismatching. These advantageous properties have so far been applied for stem cell, mesenchymal stromal cell, and chimeric antigen receptor T cell therapies. However, UCB-derived professional antigen-presenting cells are increasingly being utilized in the context of immune tolerance and regenerative therapy. Here, we review the cell-specific characteristics as well as recent advancements in UCB-based cell therapies focusing on dendritic cells, monocytes, B lymphocytes, innate lymphoid cells, and macrophages.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Antigen presentation; Cell therapy; Immune reconstitution; Umbilical cord blood

Correction:Decreased Thymic Output Contributes to Immune Defects in Septic Patients(J. Clin. Med. (2020), 9, (2695), 10.3390/jcm9092695) - Sommer, Natascha; Noack, Steffen; Hecker, Andreas; Hackstein, Holger; Bein, Gregor; Weissmann, Norbert; Seeger, Werner; Mayer, Konstantin; Hecker, Matthias (Journal of Clinical Medicine, 2022)
In the original article, there were errors in Figure 1D (panel CD8-Control). Changes are below. The authors apologize for any inconvenience caused and state that the scientific conclusions are unaffected. The original article has been updated.
CRIS-Team Scopus Importer:2022-09-30

COVID-19: Proper dosing of Convalescent Plasma in Studies Comment - Hackstein, Holger (Transfusionsmedizin, 2022)
CRIS-Team WoS Importer:2022-05-27

Das Revival der Serumtherapie Antikörper von Rekonvaleszenten sollen schwer COVID-19-Erkrankten helfen - Hackstein, Holger (Deutsche Apotheker Zeitung, 2020)
CRIS-Team Scopus Importer:2021-04-19

Decreased Thymic Output Contributes to Immune Defects in Septic Patients - Sommer, Natascha; Noack, Steffen; Hecker, Andreas; Hackstein, Holger; Bein, Gregor; Weissmann, Norbert; Seeger, Werner; Mayer, Konstantin; Hecker, Matthias (Journal of Clinical Medicine, 2020)
Background: Prolonged immunosuppression and hypoinflammation, termed compensatory anti-inflammatory response syndrome (CARS), contribute to high morbidity and mortality in the late phase of sepsis. Although apoptosis is a well-known cause of lymphopenia in sepsis, the contribution of thymic output to immune alterations in sepsis and potential compensatory mechanisms are largely unknown. Methods: We investigate the release of CD4+ T cells from the thymus and their peripheral proliferation by evaluating T-cell receptor excision circles (TREC) and the expression of CD31 as markers for recent thymic emigrants (RTE) and their proliferative offspring in septic patients with relevant lymphopenia in the CARS phase. Moreover, we determine the aging of T cells by measuring telomere characteristics. Results: In septic patients, we found decreased CD4+ T-helper cell numbers, while CD8+ T cell numbers were unchanged. As a possible cause, we detected increased apoptosis of CD4+ T-helper cells and decreased levels of IL-7, which promotes the maturation of T cells in the thymus. Accordingly, the relative number of mature CD4+ T cells, TREC-containing CD4+ T cells, and CD31+ RTEs (characteristic of thymic output) was decreased, while the relative number of CD31-T cells (peripherally expanded naive T cells) was increased. Furthermore, the telomere length decreased, although telomerase activity and markers for the shelterin complex were increased specifically in CD4+ but not in CD8+ T cells. Conclusion: We thus conclude that, in addition to T-cell apoptosis, decreased thymic output and increased aging of CD4+ T cells may contribute to lymphopenia and immunosuppression in sepsis. Increased proliferation of peripheral T cells cannot compensate for these effects.
CRIS-Team WoS Importer:2020-11-06

Deep characterization of human γδ T cell subsets defines shared and lineage-specific traits. - Sanz, Marta; Mann, Brendan T.; Ryan, Paul L.; Bosque, Alberto; Pennington, Daniel J.; Hackstein, Holger; Soriano-Sarabia, Natalia (Frontiers in Immunology, 2023)
Under non-pathological conditions, human γδ T cells represent a small fraction of CD3+ T cells in peripheral blood (1-10%). They constitute a unique subset of T lymphocytes that recognize stress ligands or non-peptide antigens through MHC-independent presentation. Major human γδ T cell subsets, Vδ1 and Vδ2, expand in response to microbial infection or malignancy, but possess distinct tissue localization, antigen recognition, and effector responses. We hypothesized that differences at the gene, phenotypic, and functional level would provide evidence that γδ T cell subpopulations belong to distinct lineages. Comparisons between each subset and the identification of the molecular determinants that underpin their differences has been hampered by experimental challenges in obtaining sufficient numbers of purified cells. By utilizing a stringent FACS-based isolation method, we compared highly purified human Vδ1 and Vδ2 cells in terms of phenotype, gene expression profile, and functional responses. We found distinct genetic and phenotypic signatures that define functional differences in γδ T cell populations. Differences in TCR components, repertoire, and responses to calcium-dependent pathways suggest that Vδ1 and Vδ2 T cells are different lineages. These findings will facilitate further investigation into the ligand specificity and unique role of Vδ1 and Vδ2 cells in early immune responses.
EVALuna2:534012

Detection of SARS-CoV-2-independent immunoregulatory activity of COVID-19 convalescent plasma - Brox, Regine; Achenbach, Susanne; Hackstein, Holger (Transfusion, 2021)
Background: Convalescent plasma has emerged as a potential specific treatment for coronavirus disease 2019 (COVID-19), since it contains severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies. Several studies are currently investigating the efficacy of convalescent plasma for treatment of COVID-19, with a focus on neutralizing antibodies. However, there is little information on whether convalescent plasma may contain additional immunoregulatory constituents produced by the blood donor during convalescence. Therefore, using a standardized whole blood assay employing synthetic toll-like receptor (TLR) ligands, we have investigated the immunoregulatory capacity of convalescent plasma in direct comparison to ABO-matched allogeneic control plasma. Study design and methods: Whole blood samples from healthy blood donors were collected, and autologous plasma was replaced by convalescent plasma or ABO-matched control plasma. Standardized innate immune triggering and monitoring was performed by adding different TLR ligands (Pam3CsK4 [TLR1/2], HKLM [TLR2], LPS [TLR4], flagellin [TLR5], ssRNA40 [TLR8], imiquimod [TLR7], and FSL-1 [TLR2/6]) and subsequent quantitative analysis of pro- and anti-inflammatory cytokines (IP-10, IL-1β, TNF-α, MCP-1, IL-6, IL-10, and IFN-γ) by cytometric bead array. Negative controls included unstimulated samples as well as samples spiked with autologous plasma. Results: COVID-19 convalescent plasma (CCP) significantly decreased pro-inflammatory cytokines production triggered by different TLR ligands in healthy donors as compared with healthy control plasma. IL-6, MCP-1, and IFN-γ represented the cytokines that are most frequently downregulated by convalescent plasma. Conclusion: Our experiments reveal a potential novel, SARS-CoV-2-independent immunomodulatory activity of CCP, which may be beneficial for COVID-19 patients.
CRIS-Team Scopus Importer:2021-10-22
Keywords: convalescent plasma; COVID-19

Die Patientenblutgruppe – der kleine, aber feine Unterschied - Zimmermann, Robert; Hackstein, Holger (Anaesthesist, 2018)
EVALuna2:213419

Distinct endocytosis and immune activation of poly lactic-co-glycolic acid nanoparticles prepared by single- and double-emulsion evaporation - Spiecker, Erdmann; Hackstein, Holger; Wu, Mingjian; Scheuer, Karl; Brox, Regine; Apeleo Zubiri, Benjamin; Pusch, Lennart; Jandt, Klaus D.; Yokosawa, Tadahiro; Fischer, Dagmar (2021)
Background: Poly lactic-co-glycolic acid (PLGA) nanoparticles can be prepared by emulsion-solvent-evaporation from o/w and w(1)/o/w(2) emulsions. Aims: To elaborate similarities and differences regarding mechanical, morphological and physicochemical properties, as well as endocytosis and dose-dependent immune responses by primary human leukocytes between nanoparticles prepared by these two methods. Methods: Fluorescently labeled as well as TLR-agonist (R848)-loaded PLGA nanoparticles were prepared via both single- and double-emulsion solvent evaporation. Results: Particles prepared by both methods were similar in chemical composition and surface charge but exhibited slight differences in size and morphology. Pronounced differences were found for loading, dissolution and mechanical properties. The particles were differently endocytosed by monocytes and induced qualitatively and quantitatively different immune responses. Conclusions: Variations in nanoparticle preparation can affect particle-derived immunological characteristics.
CRIS-Team WoS Importer:2021-09-24

Emergency Use of Convalescent Plasma: Perception of the Regulatory Framework from a Clinical Perspective - Mohnle, Patrick; Humpe, Andreas; Boeck, Markus; Gruetzner, Stefanie; Hackstein, Holger; Offner, Robert; Hildebrandt, Martin (Transfusion Medicine and Hemotherapy, 2021)
The pandemic spread of an infectious disease poses a plethora of challenges to society, clinicians, health care providers and regulating authorities. In order to mount a rapid response and to provide hope in a potentially catastrophic situation as the current COVID-19 pandemic, emergency plans, regulations and funding strategies have to be developed on regional, national and international levels. The speed needed to establish rapid response programs is challenged by the dynamics of the spread of the disease, the concurrent and competing development of different and potentially more effective treatment options, and not the least by regulatory uncertainty. Convalescent plasma, that is plasma collected from patients who have recovered from COVID-19 infections, has emerged as one of the first potential treatment options in the absence of drugs or vaccines with proven efficacy against SARS-CoV-2. The societal aspects of convalescent plasma and the public awareness gave an additional boost to the rapid employment of convalescent plasma donation platforms immediately after the SARS-CoV-2 outbreak. At the same time, uncertainty remains as to the efficacy of convalescent plasma. With evidence mostly limited to empirical reports, convalescent plasma has been used for decades for the prophylaxis and treatment of various infectious diseases. Clinical trials have addressed different infectious agents, stages of disease, target groups of patients and yielded sometimes inconclusive results. The aim of this short review is to delineate the regulatory background for the emergency use of convalescent plasma in the USA, in the European Union and in Germany, and the transition to the setting of clinical trials. In addition, we describe observations made in the process of collecting COVID-19 convalescent plasma (herein referred to as CCP), and formulate proposals to further improve the framework for rapid responses in future emergency situations.
CRIS-Team WoS Importer:2021-12-03

Erratum: Antihistone Properties of C1 Esterase Inhibitor Protect against Lung Injury - Wygrecka, Malgorzata; Wujak, Lukasz; Markart, Philipp; Kosanovic, Djuro; Müller-Redetzky, Holger C.; Witzenrath, Martin; Henneke, Ingrid; Schermuly, Ralph T.; Seeger, Werner; Schaefer, Liliana; Kwapiszewska, Grazyna; Marsh, Leigh M.; et al. (American Journal of Respiratory and Critical Care Medicine, 2022)
CRIS-Team Scopus Importer:2022-11-25

Functional Heterogeneity of Umbilical Cord Blood Monocyte-Derived Dendritic Cells - Schweiger, Petra; Hamann, Livia; Strobel, Julian; Weisbach, Volker; Wandersee, Alexandra; Christ, Julia; Kehl, Sven; Weidenthaler, Filip; Antoniadis, Sophia; Hackstein, Holger; Cunningham, Sarah (Journal of Immunology, 2024)
Human umbilical cord blood (UCB) represents a unique resource for hematopoietic stem cell transplantation for children and patients lacking suitable donors. UCB harbors a diverse set of leukocytes such as professional APCs, including monocytes, that could act as a novel source for cellular therapies. However, the immunological properties of UCB monocytes and monocyte-derived dendritic cells (MoDCs) are not fully characterized. In this study, we characterized the phenotype and functions of UCB-MoDCs to gauge their potential for future applications. UCB exhibited higher frequencies of platelets and lymphocytes as well as lower frequencies of neutrophils in comparison with adult whole blood. Leukocyte subset evaluation revealed significantly lower frequencies of granulocytes, NK cells, and CD14+CD16− monocytes. Surface marker evaluation revealed significantly lower rates of costimulatory molecules CD80 and CD83 while chemokine receptors CCR7 and CXCR4, as well as markers for Ag presentation, were similarly expressed. UCB-MoDCs were sensitive to TLR1–9 stimulation and presented quantitative differences in the release of proinflammatory cytokines. UCB-MoDCs presented functional CCR7-, CXCR4-, and CCR5-associated migratory behavior as well as adequate receptor- and micropinocytosis-mediated Ag uptake. When cocultured with allogeneic T lymphocytes, UCB-MoDCs induced weak CD4+ T lymphocyte proliferation, CD71 expression, and release of IFN-γ and IL-2. Taken together, UCB-MoDCs present potentially advantageous properties for future medical applications.<br

Generation of Reliable Red Cell Concentrate Requirement Lists for Operations and Interventions from Data Warehouse Data and Patient-Related Batch Documentation of Blood Components - Zimmermann, Robert; Becker, Andreas; Hackstein, Holger; Ganslandt, Thomas (Transfusionsmedizin, 2021)
Failure to perform transfusion-preparatory diagnostics and to order a sufficient number of blood components prior to surgery is increasingly leading to clinical emergencies and avoidable risks for patients. The mandatory preparation of blood requirement lists often fails due to the availability of suitable data. The University Hospital Erlangen is a tertiary care hospital with 1400 beds. Since 2010, all relevant data for the interpretation of patterns in the use of blood components have been continuously collected here. We are able to integrate the clinical data warehouse components of the personal data of red blood cell (RBC) recipients, the codes of inpatients in the German Diagnosis Related Group (G-DRG) system, ICD codes, OPS codes and the data of the RBC components from the blood bank's IT system. The obtained DRGs, ICD codes and OPS codes are linked to the data of blood component consumption on an individual basis. Analyses can be carried out for the entire hospital as well as for specific departments. Ongoing refinement of the database queries improves the ability to correctly estimate blood requirements for standard surgery and interventions. The results differ considerably from the surgeons' estimates of the probability of a transfusion, i.e. the probability of a transfusion is often underestimated. Correct compliance with the 10 percent transfusion probability limit for the question of early preoperative provision of cross blood can be improved by such queries. Counteracting the phenomenon of "delayed transfusion" is becoming an increasingly important task for the clinically active transfusion medicine specialist. Creating statistics on the probability of transfusion by linking data warehouse data and batch documentation data from blood banks can provide the necessary tools.
CRIS-Team WoS Importer:2021-03-26

HLA-C*04:09N is expressed at the cell surface and triggers peptide-specific T-cell activation. - Welters, Carlotta; Welters, Marthe Lina; Stadler, Serena; Bullinger, Lars; Strobel, Julian; Hackstein, Holger; Dhamodaran, Arunraj; Blankenstein, Thomas; Hansmann, Leo (Haematologica, 2024)
The null allele HLA-C*04:09N differs from HLA-C*04:01 in a frameshift mutation within its cytoplasmic domain, resulting in translation of 32 additional amino acids that are assumed to prevent cell surface expression. However, we recently identified a multiple myeloma-reactive T-cell receptor (TCR) that appeared to recognize antigen presented on HLA-C*04:09N and encouraged us to ask whether HLA-C*04:09N, albeit not easily detectable at the cell surface, can present antigen sufficient for T-cell activation. We generated two HLA-class I-deficient cell lines, re-expressed HLAC* 04:09N, detected HLA expression by flow cytometry, and tested for T-cell activation using a cytomegalovirus peptide- specific HLA-C*04:01-restricted TCR. In both cell lines, HLA-C*04:09N expression was detectable at the cell surface and could be enhanced by IFN-γ exposure. Recombinant HLA-C*04:09N expression was sufficient for T-cell activation in vitro, which could be blocked by an HLA-class I-specific antibody, suggesting HLA-TCR interaction at the cell surface. Peripheral blood mononuclear cells isolated from an individual who physiologically expressed HLA-C*04:09N triggered peptide-specific T-cell activation, confirming our results with cells with natural HLA expression levels. In conclusion, we present peptide-specific HLA-C*04:09N-restricted T-cell activation and suggest consideration of this allele in the appropriate clinical context, such as allogeneic stem cell transplantation, or in the setting of cellular therapy.
EVALuna2:540386

Human T cells loaded with superparamagnetic iron oxide nanoparticles retain antigen-specific TCR functionality. - Pfister, Felix; Dörrie, Jan; Schaft, Niels; Buchele, Vera; Unterweger, Harald; Carnell, Lucas R.; Schreier, Patrick; Stein, René; Kubánková, Markéta; Guck, Jochen; Hackstein, Holger; Alexiou, Christoph; et al. (Frontiers in Immunology, 2023)
BACKGROUND: Immunotherapy of cancer is an emerging field with the potential to improve long-term survival. Thus far, adoptive transfer of tumor-specific T cells represents an effective treatment option for tumors of the hematological system such as lymphoma, leukemia or myeloma. However, in solid tumors, treatment efficacy is low owing to the immunosuppressive microenvironment, on-target/off-tumor toxicity, limited extravasation out of the blood vessel, or ineffective trafficking of T cells into the tumor region. Superparamagnetic iron oxide nanoparticles (SPIONs) can make cells magnetically controllable for the site-specific enrichment. METHODS: In this study, we investigated the influence of SPION-loading on primary human T cells for the magnetically targeted adoptive T cell therapy. For this, we analyzed cellular mechanics and the T cell response after stimulation via an exogenous T cell receptor (TCR) specific for the melanoma antigen MelanA or the endogenous TCR specific for the cytomegalovirus antigen pp65 and compared them to T cells that had not received SPIONs. RESULTS: SPION-loading of human T cells showed no influence on cellular mechanics, therefore retaining their ability to deform to external pressure. Additionally, SPION-loading did not impair the T cell proliferation, expression of activation markers, cytokine secretion, and tumor cell killing after antigen-specific activation mediated by the TCR. CONCLUSION: In summary, we demonstrated that SPION-loading of T cells did not affect cellular mechanics or the functionality of the endogenous or an exogenous TCR, which allows future approaches using SPIONs for the magnetically enrichment of T cells in solid tumors.
EVALuna2:539766
Keywords: Adoptive T cell therapy; superparamagnetic iron oxide nanoparticles (SPIONs); antigen-specific T cell response; targeted immune therapy; cell deformability

IgA2 Antibodies against SARS-CoV-2 Correlate with NET Formation and Fatal Outcome in Severely Diseased COVID-19 Patients - Staats, Leonie A. N.; Pfeiffer, Hella; Knopf, Jasmin; Lindemann, Aylin; Fürst, Julia; Kremer, Andreas; Hackstein, Holger; Neurath, Markus; Munoz, Luis Enrique; Achenbach, Susanne; Leppkes, Moritz; Herrmann, Martin; et al. (Cells, 2020)
Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) leads to an adaptive immune response in the host and the formation of anti-SARS-CoV-2 specific antibodies. While IgG responses against SARS-CoV-2 have been characterized quite well, less is known about IgA. IgA2 activates immune cells and induces inflammation and neutrophil extracellular trap (NET) formation which may contribute to organ injury and fatal outcome in SARS-CoV-2-infected patients. SARS-CoV-2 spike protein specific antibody levels were measured in plasma samples of 15 noninfected controls and 82 SARS-CoV-2-infected patients with no or mild symptoms, moderate symptoms (hospitalization) or severe disease (intensive care unit, ICU). Antibody levels were compared to levels of C-reactive protein (CRP) and circulating extracellular DNA (ecDNA) as markers for general inflammation and NET formation, respectively. While levels of SARS-CoV-2-specific IgG were similar in all patient groups, IgA2 antibodies were restricted to severe disease and showed the strongest discrimination between nonfatal and fatal outcome in patients with severe SARS-CoV-2 infection. While anti-SARS-CoV-2 IgG and IgA2 levels correlated with CRP levels in severely diseased patients, only anti-SARS-CoV-2 IgA2 correlated with ecDNA. These data suggest that the formation of anti-SARS-CoV-2 IgA2 during SARS-CoV-2 infection is a marker for more severe disease related to NET formation and poor outcome.
CRIS-Team WoS Importer:2021-01-15

Immune Phenotypes and Target Antigens of Clonally Expanded Bone Marrow T Cells in Treatment-Naïve Multiple Myeloma - Welters, Carlotta; Lammoglia Cobo, María Fernanda; Stein, Christian Alexander; Hsu, Meng Tung; Ben Hamza, Amin; Penter, Livius; Chen, Xiaojing; Buccitelli, Christopher; Popp, Oliver; Mertins, Philipp; Dietze, Kerstin; Bullinger, Lars; et al. (Cancer Immunology Research, 2022)
Multiple myeloma is a hematologic malignancy of monoclonal plasma cells that accumulate in the bone marrow. Despite their clinical and pathophysiologic relevance, the roles of bone marrow-infiltrating T cells in treatment-naïve patients are incompletely understood. We investigated whether clonally expanded T cells (i) were detectable in multiple myeloma bone marrow, (ii) showed characteristic immune phenotypes, and (iii) whether dominant clones recognized antigens selectively presented on multiple myeloma cells. Single-cell index sorting and T-cell receptor (TCR) αβ sequencing of bone marrow T cells from 13 treatment-naïve patients showed dominant clonal expansion within CD8+ cytolytic effector compartments, and only a minority of expanded T-cell clones expressed the classic immune-checkpoint molecules PD-1, CTLA-4, or TIM-3. To identify their molecular targets, TCRs of 68 dominant bone marrow clones from five selected patients were reexpressed and incubated with multiple myeloma and non-multiple myeloma cells from corresponding patients. Only 1 of 68 TCRs recognized antigen presented on multiple myeloma cells. This TCR was HLA-C-restricted, self-peptide-specific and could be activated by multiple myeloma cells of multiple patients. The remaining dominant T-cell clones did not recognize multiple myeloma cells and were, in part, specific for antigens associated with chronic viral infections. In conclusion, we showed that dominant bone marrow T-cell clones in treatment-naïve patients rarely recognize antigens presented on multiple myeloma cells and exhibit low expression of classic immune-checkpoint molecules. Our data provide experimental context for experiences from clinical immune-checkpoint inhibition trials and will inform future T cell-dependent therapeutic strategies.
CRIS-Team Scopus Importer:2022-11-25

Immunophenotypes and Targets of clonally expanded T Cells in the Bone Marrow of Patients with acquired Aplastic Anemia - Ben Hamza, A.; Welters, C.; Bruggemann, M.; Dietze, K.; Bullinger, L.; Brummendorf, T. H.; Winkler, Thomas; Strobel, Joachim; Hackstein, Holger; Dornmair, K.; Beier, F.; Hansmann, L. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Influence of the Immune Checkpoint Inhibitors on the Hemostatic Potential of Blood Plasma - Patalakh, Iryna; Wandersee, Alexandra; Schlüter, Julian; Erdmann, Michael; Hackstein, Holger; Cunningham, Sarah (Transfusion Medicine and Hemotherapy, 2024)
Introduction: Immune checkpoint inhibitors (ICIs) have revolutionized classical treatment approaches of various cancer entities, but are also associated with a number of side effects. One of these may be life-threatening clotting disorders with the risk of thrombotic or hemorrhagic complications, the mechanisms of which are still poorly understood. In the present study, we analyzed the direct effects of pembrolizumab, nivolumab, and ipilimumab on platelet aggregation as well as plasma coagulation followed by fibrinolysis in an ex vivo model. Methods: Microplate spectrometry was used to analyze aggregation, coagulation, and fibrinolysis in platelet-free (PFP) and platelet-rich (PRP) healthy donor plasma samples treated with pembrolizumab, nivolumab, ipilimumab, and appropriate isotype controls. Aggregation was induced by TRAP-6. Clotting of PFP and PRP followed by lysis was initiated with a tissue factor in a mixture of phosphatidylserine:phosphatidylcholine and the addition of t-PA. Among other parameters, the area under the curve (AUC) was used to compare the effect of ICIs on aggregation, coagulation, and fibrinolysis. Results: Upon direct contact with platelets, pembrolizumab stimulated platelet aggregation in PRP, while nivolumab and ipilimumab promoted disaggregation with corresponding changes in the AUC. Pembrolizumab and nivolumab, both PD-1 receptor inhibitors, had no effect on the plasma coagulation cascade. Ipilimumab, a CTLA-4 receptor inhibitor, significantly increased the rate of PRP clotting. When clotting was followed by lysis, all ICIs were found to prolong the growth of the PRP-derived fibrin clot and delay its elimination. This was manifested by an increase in AUC relative to control PRP. Conclusion: This study characterizes the potential impact of pembrolizumab, nivolumab, and ipilimumab on hemostasis. Nivolumab and ipilimumab are able to reduce aggregation and increase the procoagulant properties of platelets, which can cause side effects associated with hemostatic imbalance leading to thrombosis or bleeding. The observed ICI-specific effects may contribute to our understanding of the mechanisms by which ICI affects platelets and suggest how, in a clinical setting, to reduce coagulation disorders during ICI treatment in the future
Keywords: Immune checkpoint inhibitors; Aggregation; Coagulation; Fibrinolysis; Platelet-rich plasma; Platelets; Thrombocytes

Interdependence of coagulation with immunotherapy and BRAF/MEK inhibitor therapy: results from a prospective study - Beckmann, Malte; Schlüter, Julian; Erdmann, Michael; Kramer, Rafaela; Cunningham, Sarah; Hackstein, Holger; Zimmermann, Robert; Heinzerling, Lucie (Cancer Immunology, Immunotherapy, 2024)
Immune checkpoint inhibitor (ICI) therapies effectively treat a broadening spectrum of cancer entities but induce various immune-related side effects (irAEs). Recent reports suggest a correlation between ICI-induced systemic inflammation and thromboembolic events as well as an increased effectiveness by coadministration of anticoagulants. With cancer patients having a higher risk of thrombotic events per se, it is crucial to dissect and characterize the mechanisms that cause pro-coagulative effects induced by systemic tumor therapies and their potential interplay with anti-tumor response. A total of 31 patients with advanced skin cancer treated with either ICIs (n = 24) or BRAF/MEK inhibitors (n = 7) were longitudinally assessed for blood and coagulation parameters before as well as 7, 20 and 40 days after initiation of systemic tumor therapy. Changes were analyzed and compared between both groups. In addition, the influence of coagulation parameters on progression-free, recurrence-free and overall survival was investigated. The ICI cohort presented significantly increased factor VIII activity after one week of therapy (p 0.0225); while, protein S activity was reduced during the whole observation period. Additionally, von Willebrand factor activity and tissue factor concentrations increased under immunotherapy. Similar changes occurred under BRAF/MEK inhibitor therapy (BRAF/MEKi). Increased baseline levels of von Willebrand factor antigen and factor VIII:C before the start of ICI therapy correlated with a significantly higher risk of recurrence for patients receiving adjuvant immunotherapy. The findings suggest the induction of a pro-coagulant state under ICI and BRAF/MEKi and a role of coagulation parameters in the efficacy of ICI therapie
Keywords: Immune checkpoint inhibitors; BRAF/MEK inhibitors; Melanoma; Coagulation–fibrinolysis disorders; ICI-associated thrombosis; Predictive marker

Iron Store of Repeat Plasma and Platelet Apheresis Donors - Pfeiffer, Hella; Hechler, Johannes; Zimmermann, Robert; Hackstein, Holger; Achenbach, Susanne (Clinical Laboratory, 2021)
Background: Repeat apheresis donation causes a noticeable loss of whole blood: through routine blood tests with every donation as well as through residual blood left within the used apheresis set. While the effect of blood loss on donor iron stores has been widely researched for whole blood donations, fewer and especially contradictory results exist for apheresis donors. Methods: A retrospective analysis of the donor blood samples (Department of Transfusion Medicine, University Hospital Erlangen) of the past 11 years (n = 52.976) was performed. Serum ferritin and hemoglobin were used to detect iron deficiency. Values at admission were compared to values measured at the donations. To investigate the impact of the donation frequency, this frequency was calculated for every single donor (for the whole duration of 11 years as well as for each individual year). Correlation and regression analyses between frequency and iron parameters were performed. A special group were long-time repeat donors, whose changes in ferritin values were analyzed in comparison to the first-ever ferritin value before the first donation. Results: All donor groups show significantly lower mean ferritin and hemoglobin values after repeated donations than at admission. Interestingly, there are much more iron-depleted females in the control group than there are iron-depleted males. The correlation and regression analysis showed a significant relationship between donation frequency and iron-deficiency in males, but not in females. The analysis of the long-time repeat donors showed that the relative ferritin value dropped more in males than in females. When comparing iron-depleted long-time donors, females tend to be iron-depleted much more often even before the first donation. Conclusions: Repeat apheresis donation has a noticeable effect on the iron store of the blood donor, leading to a high percentage of iron-deficient donors, especially in women. The very small correlation between donation frequency and iron depletion for females is most likely due to the fact that women tend to be iron-deficient even before the first donation. Because of the natural variation of inter-donation-intervals, the calculated donation frequency might not be that exact. As a result, the correlation between donation frequency and iron stores might be higher than suggested by this work.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Apheresis; Blood donation; Blood donor; Iron; Iron deficiency

Localization-associated immune phenotypes of clonally expanded tumor-infiltrating T cells and distribution of their target antigens in rectal cancer - Penter, Livius; Dietze, Kerstin; Ritter, Julia; Cobo, Maria Fernanda Lammoglia; Garmshausen, Josefin; Aigner, Felix; Bullinger, Lars; Hackstein, Holger; Wienzek-Lischka, Sandra; Blankenstein, Thomas; Hummel, Michael; Dornmair, Klaus; et al. (OncoImmunology, 2019)
The degree and type of T cell infiltration influence rectal cancer prognosis regardless of classical tumor staging. We asked whether clonal expansion and tumor infiltration are restricted to selected-phenotype T cells; which clones are accessible in peripheral blood; and what the spatial distribution of their target antigens is. From five rectal cancer patients, we isolated paired tumor-infiltrating T cells (TILs) and T cells from unaffected rectum mucosa (T-UM) using 13-parameter FACS single cell index sorting. TCR alpha beta sequences, cytokine, and transcription factor expression were determined with single cell sequencing. TILs and T-UM occupied distinct phenotype compartments and clonal expansion predominantly occurred within CD8(+) T cells. Expanded TIL clones identified by paired TCR alpha beta sequencing and exclusively detectable in the tumor showed characteristic PD-1 and TIM-3 expression. TCR beta repertoire sequencing identified 49 out of 149 expanded TIL clones circulating in peripheral blood and 41 (84%) of these were PD-1(-) TIM-3(-). To determine whether clonal expansion of predominantly tumor-infiltrating T cell clones was driven by antigens uniquely presented in tumor tissue, selected TCRs were reconstructed and incubated with cells isolated from corresponding tumor or unaffected mucosa. The majority of clones exclusively detected in the tumor recognized antigen at both sites. In summary, rectal cancer is infiltrated with expanded distinct-phenotype T cell clones that either i) predominantly infiltrate the tumor, ii) predominantly infiltrate the unaffected mucosa, or iii) overlap between tumor, unaffected mucosa, and peripheral blood. However, the target antigens of predominantly tumor-infiltrating TIL clones do not appear to be restricted to tumor tissue.
CRIS-Team WoS Importer:2019-04-16

Management of Pregnancy in Inherited Dysfibrinogenemia after Recurrent Miscarriage - Zimmermann, Robert; Peisl, Julia; Geisen, Christoph; Koerber, Stephanie; Achenbach, Susanne; Hackstein, Holger (Transfusionsmedizin, 2019)
Dysfibrinogenemia can lead to bleeding or thrombosis as well as to obstetric complications. The latter include early pregnancy loss, hemorrhage, placental abruption, and thrombosis. There are only a few case reports with treatment recommendations for pregnancy in affected women. We report on a meanwhile 34-year-old woman who had four consecutive early abortions between 2013 and 2015. At the presentation in our outpatient clinic, the patient reported a tendency to bruising, but no other bleeding and no thromboembolic events. Laboratory examinations showed a reduced Quick value, a prolonged thrombin time, a largely prolonged reptilase time, and fibrinogen concentrations of 0.67 g/l (Clauss method) and 3.87 g/l (immunoturbidimetry). The patient was diagnosed with dysfibrinogenemia. The molecular biological examination revealed the mutation c.103C>T. (p.Arg35Cys) in Exon 2 of the FGA gene (synonym A alpha 16Arg -> Cys substitution). During the fifth and sixth pregnancy, the patient was treated with a low-molecular heparin using the recommended prophylaxis dose for increased risk of thrombosis. At the same time, the patient received fibrinogen concentrate three times a week (3 x 2 g per week). Both pregnancies were uneventful. Poor pregnancy outcomes were reported in many cases if functionally active fibrinogen levels were less than 0.6 g/l (Clauss method). After the diagnosis of dysfibrinogenemia in a woman without an obvious tendency to bleed and without thromboembolic events in her history, it seems to us to be the best procedure to substitute fibrinogen and to applicate low-molecular-weight heparins at the same time to prevent bleeding, thrombosis, and pregnancy loss as well.
CRIS-Team WoS Importer:2019-04-12

Medium supplementation with human, but not fetal calf serum facilitates endocytosis of PLGA nanoparticles by human primary B-lymphocytes via complement opsonization - Pusch, Lennart; Brox, Regine; Cunningham, Sarah; Fischer, Dagmar; Hackstein, Holger (Biochemical and Biophysical Research Communications, 2023)
The “biological identity” of nanoparticles (NPs) is governed by a shell consisting of various biomolecules that is formed upon exposure to biological media, the so-called biomolecule corona. Consequently, supplementation of cell culture media with e.g. different sera is likely to affect interactions between cells and NPs ex-vivo, especially endocytosis. We aimed to investigate the differential impact of human and fetal-bovine serum on the endocytosis of poly (lactic-co-glycolic acid) NPs by human peripheral blood mononuclear cells via flow cytometry. Furthermore, we employed different methods to inhibit endocytosis, providing mechanistic insights. The resulting biomolecule corona was characterized via denaturing gel electrophoresis. We found profound differences between human and fetal bovine serum regarding the endocytosis of fluorescently labeled PLGA nanoparticles by different classes of human leukocytes. Uptake by B-lymphocytes was particularly sensitive. We further present evidence, that these effects are mediated by a biomolecule corona. We demonstrate to our knowledge for the first time that the complement is an important contributor to the endocytosis of non-surface-engineered PLGA-nanoparticles prepared via emulsion solvent evaporation by human immune cells. Our data demonstrates that results obtained with xenogeneic culture supplements such as fetal bovine serum may have to be interpreted with caution.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Biomolecule corona; Complement; Culture medium; Nanoparticles; PLGA

Modeling Exit Strategies from COVID-19 Lockdown with a Focus on Antibody Tests - German, Reinhard; Djanatliev, Anatoli; Maile, Lisa; Bazan, Peter; Hackstein, Holger (2020)
This paper presents two epidemiological models that have been developed in order to study the disease dynamics of the COVID-19 pandemic and exit strategies from the lockdown which has been imposed on many countries world-wide. A strategy is needed such that both the health system is not overloaded letting people die in an uncontrolled way and also such that the majority of people can get back their social contacts as soon as possible. We investigate the potential effects of a combination of measures such as continuation of hygienic constraints after leaving lockdown, isolation of infectious persons, repeated and adaptive short-term contact reductions and also large-scale use of antibody tests in order to know who can be assumed to be immune and participate at public life without constraints. We apply two commonly used modeling approaches: extended SEIR models formulated both as System Dynamics and Agent-Based Simulation, in order to get insight into the disease dynamics of a complete country like Germany and also into more detailed behavior of smaller regions. We confirm the findings of other models that without intervention the consequences of the pandemic can be catastrophic and we extend such findings with effective strategies to overcome the challenge. Based on the modeling assumptions it can be expected that repeated short-term contact reductions will be necessary in the next years to avoid overload of the health system and that on the other side herd immunity can be achieved and antibody tests are an effective way to mitigate the contact reductions for many.Competing Interest StatementThe authors have declared no competing interest.Clinical TrialThis is a simulation studyFunding StatementNo external funding was received for this researchAuthor DeclarationsAll relevant ethical guidelines have been followed; any necessary IRB and/or ethics committee approvals have been obtained and details of the IRB/oversight body are included in the manuscript.YesAll necessary patient/participant consent has been obtained and the appropriate institutional forms have been archived.YesI understand that all clinical trials and any other prospective interventional studies must be registered with an ICMJE-approved registry, such as ClinicalTrials.gov. I confirm that any such study reported in the manuscript has been registered and the trial registration ID is provided (note: if posting a prospective study registered retrospectively, please provide a statement in the trial ID field explaining why the study was not registered in advance).Yes I have followed all appropriate research reporting guidelines and uploaded the relevant EQUATOR Network research reporting checklist(s) and other pertinent material as supplementary files, if applicable.YesAll data is given in the paper directly

Notch1 Induces Defective Epithelial Surfactant Processing and Pulmonary Fibrosis. - Wasnick, Roxana; Korfei, Martina; Piskulak, Katarzyna; Henneke, Ingrid; Wilhelm, Jochen; Mahavadi, Poornima; Dartsch, Ruth Charlotte; Von Der Beck, Daniel; Koch, Miriam; Shalashova, Irina; Weiss, Astrid; Klymenko, Oleksiy; et al. (American Journal of Respiratory and Critical Care Medicine, 2023)
Rationale: Although type II alveolar epithelial cells (AEC2s) are chronically injured in idiopathic pulmonary fibrosis (IPF), they contribute to epithelial regeneration in IPF. Objectives: We hypothesized that Notch signaling may contribute to AEC2 proliferation, dedifferentiation characterized by loss of surfactant processing machinery, and lung fibrosis in IPF. Methods: We applied microarray analysis, kinome profiling, flow cytometry, immunofluorescence analysis, western blotting, quantitative PCR, and proliferation and surface activity analysis to study epithelial differentiation, proliferation, and matrix deposition in vitro (AEC2 lines, primary murine/human AEC2s), ex vivo (human IPF-derived precision-cut lung slices), and in vivo (bleomycin and pepstatin application, Notch1 [Notch receptor 1] intracellular domain overexpression). Measurements and Main Results: We document here extensive SP-B and -C (surfactant protein-B and -C) processing defects in IPF AEC2s, due to loss of Napsin A, resulting in increased intra-alveolar surface tension and alveolar collapse and induction of endoplasmic reticulum stress in AEC2s. In vivo pharmacological inhibition of Napsin A results in the development of AEC2 injury and overt lung fibrosis. We also demonstrate that Notch1 signaling is already activated early in IPF and determines AEC2 fate by inhibiting differentiation (reduced lamellar body compartment, reduced capacity to process hydrophobic SP) and by causing increased epithelial proliferation and development of lung fibrosis, putatively via altered JAK (Janus kinase)/Stat (signal transducer and activator of transcription) signaling in AEC2s. Conversely, inhibition of Notch signaling in IPF-derived precision-cut lung slices improved the surfactant processing capacity of AEC2s and reversed fibrosis. Conclusions: Notch1 is a central regulator of AEC2 fate in IPF. It induces alveolar epithelial proliferation and loss of Napsin A and of surfactant proprotein processing, and it contributes to fibroproliferation.
EVALuna2:508463

NPM-ALK-reactive T-cell responses in children and adolescents with NPM-ALK positive anaplastic large cell lymphoma - Singh, Vijay Kumar; Werner, Sebastian; Schwalm, Simone; Lennerz, Volker; Ruf, Stephanie; Stadler, Serena; Hackstein, Holger; Reiter, Alfred; Wölfel, Thomas; Damm-Welk, Christine; Woessmann, Wilhelm (OncoImmunology, 2019)
The oncoantigen nucleophosmin-anaplastic lymphoma kinase (NPM-ALK) induces cellular and humoral immune responses in patients with NPM-ALK-positive anaplastic large cell lymphoma (ALCL). We characterize the NPM-ALK-specific T-cell responses in a cohort of pediatric and adolescent ALCL-patients in remission without Human Leucocyte Antigen (HLA)-preselection. First, we assessed NPM-ALK-reactive T-cell responses and their HLA-class I restriction in patients by using dendritic cells (DCs) transfected with in vitro transcribed (IVT) NPM-ALK-RNA for CD8 (n = 20) or CD3 (n = 9) T-cell stimulation. NPM-ALK-specific T-cells were detected in twelve of 29 patients (nine of 20 with CD8-selected and three of nine with CD3-selected cells). Recognition of NPM-ALK was restricted by HLA-C alleles in six of eight, and by HLA-B alleles in four of eight analyzed patients. No NPM-ALK-reactivity was detected in 20 healthy individuals. Second, in order to define possible immunogenic NPM-ALK-epitope regions, DCs pulsed with pools of overlapping long NPM-ALK-peptides were used to stimulate T-cells in further 22 patients and ten controls. Responsive T-cells were detected in 15 patients and in five controls. A peptide pool located in the middle of the kinase domain induced ALK-reactive T-cells in 14 of 15 responsive patients. We could narrow to single peptides between p327-p370 of NPM-ALK in four patients. In conclusion, using IVT-RNA, 40% of NPM-ALK-positive ALCL-patients in remission had detectable NPM-ALK-specific T-cell responses which were mainly restricted by HLA-B and -C alleles. Peptide stimulation of T-cells revealed responses in almost 70% of patients and allowed describing an immunogenic region located in the ALK-kinase domain.
CRIS-Team Scopus Importer:2019-07-09
Keywords: ALCL; IFN-γ ELISPOT; Immune response; NPM-ALK; T-cells

Physiologically relevant aspirin concentrations trigger immunostimulatory cytokine production by human leukocytes - Brox, Regine; Hackstein, Holger (PLoS ONE, 2021)
Acetylsalicylic acid is a globally used non-steroidal anti-inflammatory drug (NSAID) with diverse pharmacological properties, although its mechanism of immune regulation during inflammation (especially at in vivo relevant doses) remains largely speculative. Given the increase in clinical perspective of Acetylsalicylic acid in various diseases and cancer prevention, this study aimed to investigate the immunomodulatory role of physiological Acetylsalicylic acid concentrations (0.005, 0.02 and 0.2 mg/ml) in a human whole blood of infection-induced inflammation. We describe a simple, highly reliable whole blood assay using an array of toll-like receptor (TLR) ligands 1-9 in order to systematically explore the immunomodulatory activity of Acetylsalicylic acid plasma concentrations in physiologically relevant conditions. Release of inflammatory cytokines and production of prostaglandin E-2 (PGE(2)) were determined directly in plasma supernatant. Experiments demonstrate for the first time that plasma concentrations of Acetylsalicylic acid significantly increased TLR ligand-triggered IL-1 beta, IL-10, and IL-6 production in a dose-dependent manner. In contrast, indomethacin did not exhibit this capacity, whereas cyclooxygenase (COX)-2 selective NSAID, celecoxib, induced a similar pattern like Acetylsalicylic acid, suggesting a possible relevance of COX-2. Accordingly, we found that exogenous addition of COX downstream product, PGE(2), attenuates the TLR ligand-mediated cytokine secretion by augmenting production of anti-inflammatory cytokines and inhibiting release of pro-inflammatory cytokines. Low PGE(2) levels were at least involved in the enhanced IL-1 beta production by Acetylsalicylic acid.
CRIS-Team WoS Importer:2021-09-10

Plasmacytoid dendritic cell depletion modifies FoxP3+ T cell homeostasis and the clinical course of bacterial pneumonia in mice - Lippitsch, Anne; Baal, Nelli; Chukovetskyi, Yuri; Cunningham, Sarah; Michel, Gabriela; Dietert, Kristina; Gurtner, Corinne; Gruber, Achim D.; Bein, Gregor; Hackstein, Holger (Journal of Leukocyte Biology, 2019)
Plasmacytoid dendritic cells (pDC) are critical to antiviral defense because of their high production of type I IFNs; less is known regarding their functions in bacterial infection. Moreover, pDC are involved in immunomodulation. A stable pool of regulatory T cells (Treg) is crucial for maintaining immune homeostasis. However, interactions between pDC and Treg regarding the regulation of Treg homeostasis are understudied. By using BDCA2-DTR mice as a systemic pDC depletion model, we identified increased steady-state numbers of FoxP3+ T cells with an effector Treg-like phenotype in lungs, liver, and spleen tissues. During sublethal, pulmonary Klebsiella pneumoniae infection, pDC deficiency also elevated respiratory FoxP3+ T cell numbers. Additionally, the improvement in acute pneumonia survival until day 5 post infection was accompanied by impaired proinflammatory cytokine production. In contrast, pDC-depleted mice exhibited a delayed clinical recovery during the post-acute phase. Therefore, we assume that pDC act as immunomodulators supporting the rapid onset of immune response in a proinflammatory manner and regulate inflammation or tissue regeneration in the post-acute phase. In summary, pDC assist in FoxP3+ T cell homeostasis and the regulation of Klebsiella-pneumonia progression.
CRIS-Team Scopus Importer:2019-07-16
Keywords: bacterial infection; BDCA2-DTR mice; immunomodulation; inflammation; Klebsiella pneumoniae; regulatory T cells

Protein S Erlangen: a novel PROS1 gene mutation associated with quantitative protein S deficiency - Schneider, Sabine; Reissig, Julian; Weisbach, Volker Günter; Achenbach, Susanne; Hackstein, Holger; Strobel, Julian (Blood Coagulation & Fibrinolysis, 2022)
The members of a Caucasian family were genetically analyzed on suspicion of hereditary protein S deficiency. A novel mutation, c.1904T>C, associated with severe quantitative protein S deficiency was found. The novel PROS1 mutation was identified by sequencing of the PROS1 gene coding sequence. The identified c.1904T>C point mutation results in p.Phe635Ser amino acid exchange, which is located in the Laminin G-like 2 domain of protein S. Computational analysis indicates that this amino acid exchange affects the correct folding of the protein S antigen. Furthermore, this mutation is located in a region of the Laminin G-like 2 domain where changes in the amino acid sequence often result in decreased secretion. We postulate that the novel p.Phe635Ser mutation might lead to an incorrect folding, and thus, to a strongly impaired secretion of this protein S variant. We named this novel variant protein.
CRIS-Team Scopus Importer:2022-06-10

Rapid generation of monocyte-derived antigen-presenting cells with dendritic cell-like properties - Cunningham, Sarah; Hackstein, Holger (Transfusion, 2021)
Background: One of the major challenges in cellular therapy is the establishment and validation of simple and fast production protocols meeting good manufacturing practice (GMP) requirements. Dendritic cells (DCs) are of particular therapeutic interest, due to their critical role in T cell response initiation and regulation. Conventional wisdom states that DC generation from monocytes is a time-consuming protocol, taking up to 7–9 days. Study Design and Methods: This study systematically screened and validated numerous culture components and conditions to identify the minimal requirements, which can give rise to functional monocyte-derived antigen-presenting cells (MoAPCs) in less than 48 h (36 h MoAPC). A total of 36 h MoAPCs were evaluated in terms of surface marker expression, endocytic capability, and induction of antigen-specific T cell expansion via flow cytometry. Results: Screening of media compositions, glucose concentrations, and surface marker kinetics, particularly DC-SIGN as a DC-specific marker, allowed the generation of DC-like APCs in 36 h (36 h MoAPCs). A total of 36 h MoAPCs displayed a similar phenotype to 48 h MoAPC and standard 7 d MoDCs in terms of HLA-DP,DQ,DR, CD83, and DC-SIGN expression, while CD1a was preferentially expressed in standard MoDCs. Functional evaluation revealed that 36 h MoAPCs displayed reduced endocytosis capabilities and IL-12p70 production. However, 36 h MoAPCs were able to induce T cell expansion both in an allogenic and antigen-specific setting. Conclusion: Our results indicate that mature 36 h MoAPCs possess DC-like capabilities by inducing antigen-specific T cell responses. This study has important implications for the generation of DC-based cellular therapies, allowing a more cost and time-efficient generation of APCs.
CRIS-Team Scopus Importer:2021-04-09
Keywords: 36 h MoAPCs; 48 h MoAPC; antigen-presenting cells; monocytes

Recent Advances in Good Manufacturing Practice-Grade Generation of Dendritic Cells - Cunningham, Sarah; Hackstein, Holger (Transfusion Medicine and Hemotherapy, 2020)
Dendritic cells (DCs) are pivotal regulators of immune responses, specialized in antigen presentation and bridging the gap between the innate and adaptive immune system. Due to these key features, DCs have become a pillar of the continuously growing field of cellular therapies. Here we review recent advances in good manufacturing practice strategies and their individual specificities in relation to DC production for clinical applications. These take into account both small-scale experimental approaches as well as automated systems for patient care.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Dendritic cells; Good manufacturing practice; Monocytes

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

SERPINC1 c.1247dupC: a novel SERPINC1 gene mutation associated with familial thrombosis results in a secretion defect and quantitative antithrombin deficiency - Ruf, Maximilian; Cunningham, Sarah; Wandersee, Alexandra; Brox, Regine; Achenbach, Susanne; Strobel, Julian; Hackstein, Holger; Schneider, Sabine (Thrombosis Journal, 2024)
BACKGROUND: Antithrombin (AT) is an important anticoagulant in hemostasis. We describe here the characterization of a novel AT mutation associated with clinically relevant thrombosis. A pair of sisters with confirmed type I AT protein deficiency was genetically analyzed on suspicion of an inherited SERPINC1 mutation. A frameshift mutation, c.1247dupC, was identified and the effect of this mutation was examined on the cellular and molecular level. METHODS: Plasmids for the expression of wild-type (WT) and mutated SERPINC1 coding sequence (CDS) fused to green fluorescent protein (GFP) or hemagglutinin (HA) tag were transfected into HEK293T cells. Subcellular localization and secretion of the respective fusion proteins were analyzed by confocal laser scanning microscopy and Western blot. RESULTS: The c.1247dupC mutation results in a frameshift in the CDS of the SERPINC1 gene and a subsequently altered amino acid sequence (p.Ser417LysfsTer48). This alteration affects the C-terminus of the AT antigen and results in impaired secretion as confirmed by GFP- and HA-tagged mutant AT analyzed in HEK293T cells. CONCLUSION: The p.Ser417LysfsTer48 mutation leads to impaired secretion, thus resulting in a quantitative AT deficiency. This is in line with the type I AT deficiency observed in the patients.
EVALuna2:553194
Keywords: Hereditary antithrombin deficiency; Secretion defect; Frameshift mutation; Thrombosis

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

The Protein S Erlangen Mutation PROS1c.1904T>C (F635S) Suppresses Secretion. - Reißig, Julian; Cunningham, Sarah; Wandersee, Alexandra; Brox, Regine; Achenbach, Susanne; Strobel, Julian; Hackstein, Holger; Schneider, Sabine (Clinical Laboratory, 2024)
BACKGROUND: The recently identified PROS1 mutation Protein S Erlangen c.1904T>C, resulting in amino acid exchange F635S, is associated with severe quantitative protein S (PS) deficiency and clinical thrombosis. It was hypothesized that this deficiency is due to a secretion defect [1]. This report aims to further elucidate the potential secretion defect of PS Erlangen. METHODS: Coding sequences (CDS) of wild type (WT) PROS1 (encoding PS) and mutated PROS1c.1904T>C (encoding PSF635S) were cloned in front of the CDS of green fluorescent protein (GFP), and the respective plasmids were introduced into HEK293T cells. PROS1-GFP and PROS1c.1904T>C-GFP expressing HEK293T cell lines were analyzed by confocal laser scanning microscopy and western blot for cellular proteins and proteins secreted to the growth medium. RESULTS: Western blot analysis revealed a significantly reduced secretion of PSF635S compared to WT PS. This observation was confirmed by the detection of mutant PSF635S-GFP fusion exclusively in the endoplasmic reticulum (ER), while PS-GFP passed through the entire secretory pathway, as indicated by the localization within both the ER and Golgi apparatus. CONCLUSIONS: The Protein S Erlangen mutation results in type I PS deficiency caused by a secretion defect.
EVALuna2:562075
Keywords: point mutation; PROS1; secretion pathway; Protein S deficiency; secretion defect

Thrombin Generation in Fresh and Frozen-Thawed Platelet Poor Plasma - Is there a Difference? - Kausche, Lea Elisabeth; Adler, Werner; Zimmermann, Robert; Hackstein, Holger; Strasser, Erwin (Clinical Laboratory, 2020)
Background: Applicability of thrombin generation tests to clinical routine has been sought for many years. The aim of this study was to compare thrombin generation measured in fresh platelet poor plasma (f-PPP) and frozen-thawed platelet poor plasma (ft-PPP) to prove the consistency of results.
CRIS-Team WoS Importer:2020-07-17

Thrombocyte apheresis cassettes as a novel source of viable peripheral blood mononuclear cells - Cunningham, Sarah; Buchele, Vera; Brox, Regine; Strasser, Erwin; Hackstein, Holger (Transfusion, 2020)
BACKGROUND: Traditionally, white blood cells (WBCs) are collected from buffy coats or freshly drawn blood. However, the increasing demand for peripheral blood mononuclear cells (PBMCs) in the research phases of immunological therapy development makes it necessary to identify alternative sources of these cells. STUDY DESIGN AND METHODS: Leukapheresis products are cost intensive and not offered by all blood banks. Therefore, thrombocyte apheresis cassettes (TACs), plateletpheresis waste products, were investigated as a possible low-cost and easily accessible blood source for research laboratories. The recovery rate, phenotype, and functionality of WBC subsets from TAC are unknown and were investigated in comparison to frequently used blood resources via flow cytometry. RESULTS: On average, TACs provide 30.3 × 106/mL PBMCs, situating themselves between peripheral whole blood (WB; 5.35 × 106/mL) and leukoreduction system chamber (LRSC; 163.9 × 106/mL) yields. Frequencies of CD14, CD3, CD4, CD8, CD56, CD19, and CD11c positive cells in TACs correlate with normal proportions of WBC populations. Stimulation of TAC-derived PBMCs by lipopolysaccharide (LPS) and resiquimod (R848) showed no significant differences in expression levels of human leukocyte antigen (HLA)-DR, DQ, DP, and CD86 or cytokine secretion compared to other blood source derived PBMC. Following stimulation with LPS or R848, comparable levels of tumor necrosis factor-α, interleukin-10, and interleukin-1β could be measured between TAC, LRSC, and WB. Additionally, TAC-derived T cells retained their proliferation capability and were able to produce interferon-γ following T-cell receptor stimulation. CONCLUSION: TACs provide a cost-effective source of viable and functional human blood cells that can readily be used for clinical and laboratory investigations after plateletpheresis preparation.
CRIS-Team Scopus Importer:2020-03-27

Validation of a Parvovirus B19 NAT Assay for Screening of Umbilical Cord Blood for Allogenic Hematopoietic Stem Cell Donation - Steininger, Philipp; Korn, Klaus; Hackstein, Holger; Strasser, Erwin F. (Transfusion Medicine and Hemotherapy, 2023)
Introduction: Parvovirus B19 transmitted by umbilical cord blood (UCB) products may cause severe disease in allogenic hematopoietic stem cell transplant recipients. Thus, commercially available nucleic acid test (NAT) assays for highly sensitive detection of parvovirus B19 DNA validated for the specimen cord blood plasma (CBP) are required to avoid parvovirus B19 transmission by umbilical hematopoietic stem cell preparations. Methods: The multiplex cobas DPX NAT assay was validated for detection of parvovirus B19 DNA in CBP derived from citrate anticoagulated UCB units which have been processed by the Rubinstein method. In total, 363 retained CBP samples pretested negative for parvovirus B19 DNA were prepared for analyzing sensitivity, specificity, and interference of that NAT assay. The 3rd WHO International Standard for parvovirus B19 DNA was used for determining the 95% limit of detection (LOD95) by probit analysis. Results: The validation of the parvovirus B19 NAT assay for CBP demonstrated high sensitivity, specificity, intra- and inter-assay precision. Dilution series and replicate analyses showed a high linearity of the assay with a coefficient of determination above 0.99 and revealed a LOD95 of 17 International Units (IU)/mL (95% confidence interval, 14-44 IU/mL) for parvovirus B19 DNA in CBP samples. Conclusion: The validation of a commercially available parvovirus B19 NAT assay for the specimen CBP demonstrated a high assay performance fulfilling German guidelines and international regulations.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Allogenic hematopoietic stem cell donation; Nucleic acid test screening; Parvovirus B19; Umbilical cord blood

Validation of a SARS-CoV-2 RNA RT-PCR assay for high-throughput testing in blood of COVID-19 convalescent plasma donors and patients - Strasser, Erwin; Steininger, Philipp; Korn, Klaus; Achenbach, Susanne; Tenbusch, Matthias; Cunningham, Sarah; Zimmermann, Robert; Überla, Klaus; Hackstein, Holger (Transfusion, 2020)
Background The frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNAemia in blood donors is uncertain. Thus, assays for SARS-CoV-2 RNA detection in blood, validated on commercially available polymerase chain reaction (PCR) systems, are required to allow a good comparability of data.
CRIS-Team WoS Importer:2020-11-27

Virus-reactive T cells expanded in aplastic anemia eliminate hematopoietic progenitor cells by molecular mimicry - Ben Hamza, Amin; Welters, Carlotta; Stadler, Serena; Brüggemann, Monika; Dietze, Kerstin; Brauns, Olaf; Brümmendorf, Tim H.; Winkler, Thomas; Bullinger, Lars; Blankenstein, Thomas; Rosenberger, Leonie; Leisegang, Matthias; et al. (Blood, 2024)
Acquired aplastic anemia is a bone marrow failure syndrome characterized by hypocellular bone marrow and peripheral blood pancytopenia. Frequent clinical responses to calcineurin inhibition and antithymocyte globulin strongly suggest critical roles for hematopoietic stem/progenitor cell–reactive T-cell clones in disease pathophysiology; however, their exact contribution and antigen specificities remain unclear. We determined differentiation states and targets of dominant T-cell clones along with their potential to eliminate hematopoietic progenitor cells in the bone marrow of 15 patients with acquired aplastic anemia. Single-cell sequencing and immunophenotyping revealed oligoclonal expansion and effector differentiation of CD8+ T-cell compartments. We reexpressed 28 dominant T-cell receptors (TCRs) of 9 patients in reporter cell lines to determine reactivity with (1) in vitro–expanded CD34+ bone marrow, (2) CD34− bone marrow, or (3) peptide pools covering immunodominant epitopes of highly prevalent viruses. Besides 5 cytomegalovirus-reactive TCRs, we identified 3 TCRs that recognized antigen presented on hematopoietic progenitor cells. T cells transduced with these TCRs eliminated hematopoietic progenitor cells of the respective patients in vitro. One progenitor cell–reactive TCR (11A5) also recognized an epitope of the Epstein-Barr virus–derived latent membrane protein 1 (LMP1) presented on HLA-A∗02:01. We identified 2 LMP1-related mimotopes within the human proteome as activating targets of TCR 11A5, providing proof of concept that molecular mimicry of viral and self-epitopes can drive T cell–mediated elimination of hematopoietic progenitor cells in aplastic anemia.
CRIS-Team Scopus Importer:2024-03-08